Root Morphological Characters at Several Distances from Irrigated Trench in Rice Varieties Grown under Rain-fed Conditioned Plots - Asia Arifin; Rinaldi Sjahril; Muhammad Riadi; Naoya Arita; Akira Miyazaki (Hasanuddin University, 2018)
In rain-fed area, water deficit or drought stress is a serious limiting factor to rice production and yield stability, and root system with deep roots is one of the most important characters. This study aimed to identify which root morphological characters induce the advantage of the deep rooting between varieties. Six varieties consisting of two groups of ecosystems, upland: NERICA1, NERICA4, NERICA7, Yumenohatamochi, and lowland: Hinohikari and Koshihikari were grown under the rain- fed condition in the field of Kochi University. The results suggested the adaptability of NERICA varieties to the upland rainfed conditions, due to the development of roots into the deep soil layer. NERICA7 had lowest soil moisture content and had a higher root weight, root surface area, root length and the number of root branching in the deep soil layer at heading stage. NERICA7 also had higher value on dry weight, surface area and thickness in total amount of root morphological characters. Varietal difference of root surface area in the deep soil layer was related to both root length and thickness, and root length was involved with root branches. On the other hand, the varietal difference of total amount of root surface area was related not to the root length, but to the root thickness. This result suggested that the emergence of the thick roots (probably primary crown roots) allowed the roots to penetrate into the deep soil layer. Therefore, it is considered that the emergence of thick roots is an important trait for the deep rooting character.